Application of Postoperative Remote Follow-Up of CIED Based on the 5G Cloud Technology Support Platform in Areas With Underdeveloped Medical Resources - Tong, Lin; Long, Yu; Xiong, Shiqiang; Li, Jin; Huang, Wenchao; Liu, Hanxiong; Cai, Lin (Frontiers in Cardiovascular Medicine, 2022)
Postoperative follow-up is crucial for the clinical management of patients carrying cardiovascular implantable electronic devices (CIED). However, in a plethora of underdeveloped areas of China, due to limited medical resources and associated economic costs, geographical restrictions, the outbreak of Coronavirus Disease 19 (COVID-19) pandemic, and other various reasons, the medical system is unable to meet the ever-increasing demand of long-term clinical follow-up and telemedicine services. Based on these challenges, postoperative remote follow-up of CIED based on 5G-cloud technology support platform (5G-CTP), may have the potential to optimize the allocation of medical resources and provide patients high-quality CIED follow-up services locally. These unique characteristics of CIED follow-up utilizing 5G-CTP are qualified to protect the safety of the patients, in terms of both clinical safety and cyber security. Furthermore, during COVID-19 pandemic, remote follow-up of CIED significantly reduces the risk of viral exposure of patients and medical staff, while having the potential to improve the current situation of CIED postoperative follow-up.